Overexpression of OsMYBS1 affect leaf morphology, photosynthesis, and agronomic performance in rice - Ma, Yinhua; Zhang, Jing; Liang, Kai; Huang, Anqi; Liu, Jingshu; Li, Weiwei; Sun, Bin; Zhao, Yan (Frontiers in Plant Science, 2025)
MYB transcription factors are critical regulators of plant growth, development, and responses to environmental stresses. However, the role of OsMYBS1, a MYB-related transcription factor in rice (Oryza sativa), in modulating plant morphology and agronomic traits remains largely unexplored. In this study, we investigated the biological function of OsMYBS1 by generating overexpression lines in rice. Our results demonstrated that overexpression of OsMYBS1 led to pronounced morphological and physiological alterations, including reduced plant height, broader and yellowing flag leaves, and decreased chlorophyll content. Agronomic evaluations further revealed that overexpression lines produced more tillers and panicles, with a reduced seed-setting rate but without a decrease in total grain yield per plant. Transcriptomic analysis identified a substantial number of differentially expressed genes (DEGs) associated with chloroplast biogenesis, photosynthesis, and metabolic processes, indicating that OsMYBS1 may influence chloroplast development and function. Collectively, these findings suggest that OsMYBS1 functions as a multifunctional regulator of plant growth and development, modulating leaf morphology and key agronomic traits. Our study provides a foundation for future investigations into the molecular mechanisms governed by OsMYBS1 and its potential utility in rice breeding to improve key agronomic traits.